ESTIMATION DES BESOINS EN EAU DE LA CULTURE DE Lâ€™AIL PAR DIFFERENTES FORMULES - Kenza, Kadi; Manel, Chergui; Nabila, Malkia; Sofia, Hamli; Sabah, Boukeria; Abdelouahab, Yahia (European Scientific Journal, ESJ, 2014)
This research focuses on the estimated water requirements of growing garlic (Allium sativum L.) variety MessidrÃ´me and determining its impact on the behavior of plants. We chose 04 methods to estimate the need for determining PET namely; PET wilaya Oum El Bouaghi (T1), evaporation of Piche (EVP, T2), the formula Blanney Criddle (T3), and the formula for Bouchet (T4) compared with non-irrigated control. To get a good garlic production with an optimum size of bulbs based on estimate irrigation through Blanney Criddle formula takes consideration of lighting and average temperature